Status of Seed Discoloration of Rice, Mycoflora Associated and its Impact on Seed Health and Quality of Farmer Saved Seeds - ANJU BALA,; PPS PANNU, (Seed Research, 2026)
Seed discoloration of rice due to infection by different fungi leads to problems in seed certification programme. This study was performed on seed samples of 20 cultivars collected from different districts of Punjab, Haryana and Rajasthan. Average disease incidence per cent from all districts was maximum on variety PR 124 (33.37%) followed by Pusa 44 (31.16) and PR 118 (28.18). Highest incidence of discoloration was 64% in PR 124 sample obtained from district Jalandhar followed by variety Pusa 44 from Moga and HKR 47 from Fatehgarh Sahib where the incidence was 41.41 and 40.08 % respectively. For testing germination and vigour of seedlings, the discolored seeds were separated and divided into four different categories based on percent area of discoloration. Seedling test was carried out using in-between blotter paper method. Seed mycoflora associated with discoloration was isolated from discolored grains. Among the field fungi, maximum of Curvularia lunata followed by Alternaria alternata, Drechslera oryzae and Fusarium species was recorded. Among the storage fungi, Aspergillus flavus dominated over other fungi; A. niger, Penicillum spp., Chetomium spp. and Rhizopus spp. Seed germination, root length, shoot length, dry weight of the seedlings and seedling vigour was significantly reduced by increase in percent area of discoloration. Seed germination was below seed certification standard (80%) when intensity of discoloration was >50%. Discolored seeds gave rise to seed rot, produced stunted and blighted seedlings. Therefore, it is suggested to avoid using discolored seeds for sowing purpose.